2021
DOI: 10.1101/2021.02.28.432901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small molecule SWELL1-LRRC8 complex induction improves glycemic control and nonalcoholic fatty liver disease in murine Type 2 diabetes

Abstract: Type 2 diabetes (T2D) is associated with insulin resistance, impaired insulin secretion from the pancreatic β-cell, and nonalcoholic fatty liver disease (NAFLD). SWELL1 (LRRC8a) ablation impairs adipose and skeletal muscle insulin-pAKT2 signaling, β-cell insulin secretion and glycemic control - suggesting that SWELL1-LRRC8 complex dysfunction contributes to T2D pathogenesis. Here, we show that ICl,SWELL and SWELL1 protein are reduced in adipose and β-cells in murine and human T2D. Combining cryo-electron micro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…Our lab has only begun to better understand how native VRAC may be modulated by small-molecule compounds utilizing the robust YFP-quenching assays previously established as a functional readout of chloride channel activity [ 72 , 82 ]. Others have used cryo-EM to identify putative binding sites of small-molecule VRAC inhibitors and using the gained structural insight to develop even more potent channel blockers [ 12 , 22 ]. Protein engineering approaches have generated LRRC8 chimeras that may serve as a complementary approach to identify putative binding sites of known VRAC modulators [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has only begun to better understand how native VRAC may be modulated by small-molecule compounds utilizing the robust YFP-quenching assays previously established as a functional readout of chloride channel activity [ 72 , 82 ]. Others have used cryo-EM to identify putative binding sites of small-molecule VRAC inhibitors and using the gained structural insight to develop even more potent channel blockers [ 12 , 22 ]. Protein engineering approaches have generated LRRC8 chimeras that may serve as a complementary approach to identify putative binding sites of known VRAC modulators [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic beta cells, VRAC enhances insulin secretion following glucose uptake suggesting the channel could be a novel drug target for type 2 diabetes. In support of this idea, Sah and colleagues recently reported that a small molecule that enhances the stability of VRAC in the cell membrane promotes glucose responsiveness and insulin release from beta cells [ 22 ]. Whether or not a frank activator of VRAC would have similar effects is not yet known.…”
Section: Overview Of the Volume-regulated Anion Channel (Vrac)mentioning
confidence: 99%